Bench Scale Calorimetry in Chemical Reaction Kinetics : An Alternative Approach to Liquid Phase Reaction Kinetics - Litz, Wilfried (Springer International Publishing : Imprint: Springer, 2015)
This book describes new and efficient calorimetric measurement methods, which can be used to accurately follow the chemical kinetics of liquid phase reaction systems. It describes apparatus and techniques for the precise measuring of the rate of heat liberation in discontinuous and continuous isothermal as well as non-isothermal reactions. The presented methodology can be used to follow the development of chemical reactions online, even in industrial scales. Written by an experienced scientist and practitioner, who can look back on long-standing expert knowledge in chemical engineering, the book contains many practical hints and instructions. The reader will find a sound compact introduction to fundamentals, and comprehensive technical background information and instructions for performing own kinetic experiments. This book is the fusion of scientific background information and long hands-on experience in the practice.  .